2012
DOI: 10.1016/j.jpainsymman.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Frequency and Treatment of Restless Legs Syndrome in a Palliative Care Unit

Abstract: In the free-text items, the most frequently cited strength of the ESAS-r was that it is easier to complete or clearer than the ESAS (n ¼ 20). Multiple suggestions for improvement were made, with the most common being a need to clarify the ''lack of appetite'' descriptor (n ¼ 5) and making the tool easier for particular groups of patients to use, for example, those with a lower level of schooling (n ¼ 5).Although the response rate was moderately low, palliative care providers who responded to the survey had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
2
0
2
Order By: Relevance
“…[151631] Lesser prevalence has been reported in subjects undergoing palliative care, probably related to use of opioid therapy during palliation. [14] Anemia is common in patients suffering from cancer, as also seen in the present study [Table 2]. [41] Cancer leads to either absolute or functional deficiency of iron.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[151631] Lesser prevalence has been reported in subjects undergoing palliative care, probably related to use of opioid therapy during palliation. [14] Anemia is common in patients suffering from cancer, as also seen in the present study [Table 2]. [41] Cancer leads to either absolute or functional deficiency of iron.…”
Section: Discussionsupporting
confidence: 75%
“…Reported the prevalence of RLS among subjects with malignancy varies between 0.87% to 18.3%. [1415] In these patients, female gender and antineoplastic therapy for at least 3 months were predictors of RLS. [15] Patients with RLS have a higher level of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Only one other study has reported on RLS in a palliative care population, and that study examined patients admitted to an inpatient palliative care unit (24). Surprisingly, of the 296 patients interviewed, only 3 (1 percent) fulfilled the main diagnostic criteria for RLS; 77 percent of the study population was made up of patients with advanced malignancy, an additional 13 percent had neurodegenerative diseases, and the remaining 10 percent had nonmalignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Die Prävalenz von RLS-Beschwerden bei Palliativpatienten ist bisher nur wenig untersucht und wird je nach Population sehr unterschiedlich angegeben. Zwischen 1 und 50 % der Palliativpatienten berichten RLS-Beschwerden[823,824]. Möglicherweise liegt die Spanne der berichteten Beschwerden an den unterschiedlichen Stadien der Erkrankung und der Frage, ob die Patienten bereits Opioide für die Grunderkrankung erhalten, was die RLS-Beschwerden gut therapieren würde.…”
unclassified
“…Diese Therapieprinzipien unterscheiden sich nicht grundsätzlich bei der Therapie von Patienten mit nicht-heilbaren Krebserkrankungen, jedoch bestehen hier sehr wahrscheinlich deutliche synergistische Therapiemöglichkeiten.Es ist klinisch zu erwarten, dass Opioidtherapien bei Krebspatienten (Schmerz, Atemnot) ein mögliches RLS gut behandeln könnten. Möglicherweise ist dies der Grund für die sehr variablen Prävalenz des RLS bei Krebspatienten[823,824]. Ein weiteres mögliches synergistisches Therapiekonzept ist durch Pregabalin und Gabapentin gegeben.…”
unclassified